Environmental microdosimetry: microdosimetric characterisation of low-dose exposures. Issue 1 (16th April 2015) - Waker, A. J.; Mahilrajan, T.; Sandhu, H.
Abstract : A number of researchers, as well as the International Commission on Radiation Units and Measurements, have described how concepts and quantities used in microdosimetry best capture the stochastic nature of low-level exposures in terms of cell hits and the fraction of cells affected within a tissue. However, the concepts of microdosimetry are not generally intuitive to the public or indeed to health physicists. In this article, the methods of conventional internal dosimetry was applied to different forms of radioactive iodine to derive cell-hit numbers and cell fractions affected by low-level exposures, and it is shown that microdosimetric analysis is compatible with conventional dosimetry but has the advantage of underscoring the stochastic nature of ionising radiation at low dose. The microdosimetric description of low-dose exposures derived in this work could be improved with the use of Monte Carlo track structure codes and more realistic models of different tissues and their cellular structure.